Effects of fresh and fermented olive oil solid waste on nitrogen use efficiency in wheat: A dataset(Mendeley Data). - Abd Al Karim Jaafar; Akram Al-Balkhi; Andrés Rodríguez-Seijo (Data in Brief, 2025)
Olive Oil Solid Waste (OSW) is a valuable agricultural by-product that can be used as a source of organic matter and nutrients for crops. However, the efficiency of OSW in providing nitrogen to plants depends on its decomposition rate and how nitrogen is available. Here, we investigated the nitrogen utilization coefficient (NUC) from fresh and fermented OSW added to calcareous soil planted with durum wheat (Triticum durum cv Sham 3). Our data showed that the NUC of fermented OSW was significantly higher than that of fresh OSW, with values of 50.15 % and 35.36 %, respectively. This difference was attributed to the enhanced biodegradation of fermented OSW, which resulted in the release of more nitrogen in a form that was readily available for plants.